QuickVR: A standard library for virtual embodiment in unity - Oliva, Ramon; Beacco, Alejandro; Navarro, Xavi; Slater, Mel (Frontiers in Virtual Reality, 2022)
In the last few years the field of Virtual Reality (VR) has experienced significant growth through the introduction of low-cost VR devices to the mass market. However, VR has been used for many years by researchers since it has proven to be a powerful tool across a vast array of research fields and applications. The key aspect of any VR experience is that it is completely immersive, which means that the virtual world totally surrounds the participant. Some game engines such as Unity already support VR out of the box and an application can be configured for VR in a matter of minutes. However, there is still the lack of a standard and easy to use tool in order to embody participants into a virtual human character that responds synchronously to their movements with corresponding virtual body movements. In this paper we introduce QuickVR, a library based on Unity which not only offers embodiment in a virtual character, but also provides a series of high level features that are necessary in any VR application, helping to dramatically reduce the production time. Our tool is easy to use by coding novices, but also easy extensible and customizable by more experienced ones.